Comprehensively Analyzed Macrophage-Regulated Genes Indicate That PSMA2 Promotes Colorectal Cancer Progression - Qi, Jingbo; Hu, Zhiqiu; Liu, Shaoqun; Li, Fan; Wang, Sheng; Wang, Wuqing; Sheng, Xia; Feng, Li (Frontiers in Oncology, 2021)
Colorectal cancer (CRC) is the third most common cancer worldwide. Here, we identified tumor-associated macrophages (TAMs) as regulators of genes in CRC. In total, the expressions of 457 genes were dysregulated after TAM coculture; specifically, 344 genes were up-regulated, and 113 genes were down-regulated. Bioinformatic analysis implied that these TAM-related genes were associated with regulation of the processes of macromolecule metabolism, apoptosis, cell death, programmed cell death, and the response to stress. To further uncover the interplay among these proteins, we constructed a PPI network; 15 key regulators were identified in CRC, including VEGFA, FN1, JUN, CDH1, MAPK8, and FOS. Among the identified genes, we focused on PSMA2 and conducted loss-of-function experiments to validate the functions of PSMA2 in CRC. To further determine the mechanism by which PSMA2 affected CRC, we conducted multiple assays in CRC cell lines and tissues. PSMA2 enhanced the proliferation, migration and invasion of CRC cells. Moreover, our data indicated that PSMA2 expression was dramatically increased in stage 1, stage 2, stage 3, and stage 4 CRC samples. Our data indicated that PSMA2 was one target of miR-132. A miR-132 mimic greatly hindered CRC cell proliferation. In addition, the luciferase assay results revealed that miR-132 directly regulated PSMA2. Moreover, our data indicated that miR-132 expression was greatly decreased in CRC samples, which was associated with longer survival times of CRC patients, implying that miR-132 was a probable biomarker for CRC. Collectively, these data indicate that PSMA2 is a promising target for the therapy of CRC.